HYPOTHERMIA AND ASSOCIATED FACTORS AMONG PATIENTS RECEIVING CONTINUOUS RENAL REPLACEMENT THERAPY AT SAINT-PAUL GENERAL HOSPITAL, 2025–2026 (Vietnam Journal of Community Medicine, 2026)
Introduction: Hypothermia is a common complication but has not received adequate attention in patients undergoing continuous renal replacement therapy (CRRT).Objective:To determine the prevalence and several factors associated with hypothermia in patients undergoing continuous renal replacement therapy at the Intensive Care and Toxicology Department and the Surgical Intensive Care Unit of Saint Paul General Hospital.Methods: A prospective descriptive study was conducted on 67 patients indicated for continuous renal replacement therapy (CRRT).Results: The incidence of hypothermia during continuous renal replacement therapy (CRRT) was 29.8% (20 patients). Among patients who developed hypothermia, the majority experienced moderate (34.0–
Keywords: Hypothermia; Extracorporeal dialysis; CRRT; Intensive care and toxicology.